PENELITIAN PERSEPSI PEJALAN KAKI DI WILAYAH KAMPUS UNIVERSITAS INDONESIA - Alyani, Ilma; Sumabrata, R. Jachrizal (FSTPT Indonesia, 2015)
Currently walking is still not being a favorite way to transport in our society. Therefore, this research explored the opinions of people about the activity of walking itself. Different from any researches before, this research tried qualitative approach to explore the reasons why people are interested in and not interested in walking. The research was conducted using web-based questionnaire (online survey). After filtered, processed data includes the reasons why people are interested in and not interested in walking. Then this data analyzed using descriptive statistics and Chi-square correlation test using SPSS software. The test results showed that there is no significant correlation was found between gender and the reasons people are interested and not interested in walking.